NGHIÊN CỨU SỬ DỤNG NẤM CỘNG SINH ABUSCULAR MYCORHIZA ĐỂ NÂNG CAO HIỆU QUẢ XỬ LÍ ĐẤT NHIỄM CHÌ CỦA CÂY NGÔ - Chính, Tăng Thị; Cường, Bùi Văn (Vietnam Journal of Science and Technology, 2012)
APPLICATION THE ABUSCULAR MYCORRHIZAS FUNGI FOR ENHANCEMENT LEAD UPTAKE FROM Pb-CONTAMINATED SOIL BY MAIZE Utilizing plant to eliminate heavy metal from contaminated-soil has been being studied and applied in many countries throughout the world. The advantages of this method are considered as: cost-effective, applicable to a large contaminated site and friendly to environment. In this report, the role of Arbuscular mycorrhizas (AM) on the tolerance and lead (Pb) absorbable of maize culturing in Pb polluted-soil were evaluated. After nine weeks culturing, the results showed that the dry weight of the AM-inoculated maize is six fold higher than this of the non AM-inoculated maize. And the amount of Pb accumulation in the AM-inoculated maize dry biomass is also threefold higher than in the non AM-inoculated maize. From the obtained data indicated that the AM fungi significantly enhanced the growth and Pb absorption of maize. And the high concentration of Pb (2000 ppm Pb) in culturing soil was decreased the symbiont of AM fungi in maize's root and the total count of microorganisms in the experiment soil.